Pengaruh Inovasi Dan Kualitas Produk Terhadap Loyalitas Konsumen Yang Dimediasi Oleh Kualitas Pelayanan Di Gacoan Cabang Tlogomas (Studi Empiris Pada Mahasiswa UNISMA) - Wulandari, Devfi; Basalamah, Muhammad Ridwan; Athia, Ita (E-JRM : Elektronik Jurnal Riset Manajemen, 2025)
Abstract This study aims to determine the effect of innovation and product quality on consumer loyality mediated by service quality among consumers of Champion Noodles Tlogomas Branch, particularly students of the Islamic University of Malang. A quantitative approach with explanatory research design was employed. The sample consisted of 75 respondents selected using purposive sampling. Data were collected through questionnaires and analyzed using Structural Equation Modeling (SEM) with the SmartPLS software. The results show that innovation and product quality significantly influence consumer loyalty, both directly and through the mediation of service quality. Service quality also has a significant effect on consumer loyalty. These findings suggest that Champion Noodles management should continuously enhance innovation, product quality, and service excellence to maintain customer loyalty. Moreover, service quality plays a crucial mediating role, reinforcing the relationship between innovation and product quality on consumer loyalty. These findings suggest that to maintain consumer loyalty, Mie Gacoan should focus on continuous product innovation, maintaining high product standards, and delivering excellent service. Keywords: Innovation, Product Quality, Service Quality, Consumer Loyalty